British-born Black African youth and educational social capital - Messele, Alganesh (New York : Routledge, 2020)
"This book examines the extent to which British-born Black African youth have access to opportunities and support during their pre-school, primary school and secondary school years. Through the voice of British-born Black African youth, this book explores why and how some racial-ethnic and linguistic minority students fail academically while students from other linguistic minorities excel despite coming from similar socioeconomic backgrounds. Drawing on interpretive-qualitative research analysis, the author demonstrates the racial dimension of social capital in education that challenges the traditional social capital theory that recodes structural notions of racial inequality as primarily cultural, social, and human capital processes and interactions. In contrast to the typical focus on achievement gaps, the concept of opportunity gaps shows how and why language policies have shaped the educational experiences and outcomes of linguistic minority students. This book will be of interest to policy makers, practitioners and scholars of Multicultural Education, Black and African Diaspora Studies and Educational Sociology"--
Introduction -- Theoretical framework -- Ethiopians and Eritreans in London -- Social capital within school -- Classroom-based social capital -- Parental involvement as social capital -- Implications for policy and practices.
OCLC-licensed vendor bibliographic record.
Keywords: Discrimination in education -- Great Britain; Youth, Black -- Education -- Great Britain; Linguistic minorities -- Education -- Great Britain; Human capital -- Great Britain; EDUCATION / Multicultural Education